The changing boys' world in the 20th century: reality and “fiction” - Bereska, Tami (My University, 2003)
In university and college classrooms today gender is a hot topic and the issue that raises the most discussion is that of how much gender roles have changed or remained the same. This issue has been studied among both adults and adolescents over the last several decades in a variety of ways including analyses of popular cultural representations. However, more research has been done on representations of femininity than on masculinity in adolescent popular cultural products, and the area of young adult literature has been relatively ignored by social scientists. This paper presents the results of a study exploring the structure of masculinity in young adult novels for boys from the 1940s through the 1990s. Over this 50-year period, the components that make up the structure of masculinity remain static, indicating that at least a portion of the discourse on masculinity has remained unchanged for more than 50 years. This has implications not only for the lives of boys and men today, but also for the maintenance of patriarchy itself. In trying to create equity in society, we appear to have focused all of our attention on the girls' world, but left the boys' world virtually untouched.
Keywords: young adult literature; masculinity in literature; boys in literature